Flavones from the Bark of Lindera caudata and Their Anti‐Tobacco Mosaic Virus Activity. (16th March 2015) - Yang, Yu‐Chun; Qin, Ying; Wu, Xian‐Xue; Xia, Cong‐Fang; Meng, Yan‐Lin; Zhou, Bin; Ye, Yan‐Qing; Gao, Xue‐Mei; Li, Yin‐Ke; Hu, Qiu‐Fen
<x xml:space="preserve">Abstract</x> Two new flavones, 5‐hydroxy‐8‐hydroxymethyl‐7, 4′‐dimethoxy‐flavone (1) and 6‐hydroxy‐8‐hydroxymethyl‐7, 4′‐dimethoxy‐flavone (2), together with six known flavones (3–8), were isolated from the bark of Lindera caudata. The structures of 1–8 were elucidated by spectroscopic methods including extensive 1D and 2D NMR techniques. Compounds 1–8 were evaluated for their anti‐tobacco mosaic virus (anti‐TMV) activity. The results showed that Compounds 1 and 2 showed high anti‐TMV activity with inhibition rates of 31.2 and 28.8%, respectively. These values are close to those of positive control.